2000
DOI: 10.1074/jbc.275.18.13476
|View full text |Cite
|
Sign up to set email alerts
|

Munc18-2, a Functional Partner of Syntaxin 3, Controls Apical Membrane Trafficking in Epithelial Cells

Abstract: The Sec1-related proteins bind to syntaxin family tSNAREs with high affinity, thus controlling the interaction of syntaxins with their cognate SNARE partners. Munc18-2 is a Sec1 homologue enriched in epithelial cells and forms a complex with syntaxin 3, a t-SNARE localized to the apical plasma membrane. We generated here a set of Munc18-2 point mutants with substitutions in conserved amino acid residues. The mutants displayed a spectrum of different syntaxin binding efficiencies. The in vitro and in vivo bindi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
72
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(80 citation statements)
references
References 59 publications
7
72
1
Order By: Relevance
“…2 A, B). The NV mutants of both isoforms were less abundant than the corresponding WT variants, indicating that the NV mutation decreases the stability of Munc18, as reported previously for Munc18-2 (Riento et al, 2000). Nevertheless, all Munc18 variants were expressed in excess of native Munc18-1 in chromaffin cells.…”
Section: Expression Of the Munc18 Variants In Chromaffin Cellsmentioning
confidence: 51%
See 1 more Smart Citation
“…2 A, B). The NV mutants of both isoforms were less abundant than the corresponding WT variants, indicating that the NV mutation decreases the stability of Munc18, as reported previously for Munc18-2 (Riento et al, 2000). Nevertheless, all Munc18 variants were expressed in excess of native Munc18-1 in chromaffin cells.…”
Section: Expression Of the Munc18 Variants In Chromaffin Cellsmentioning
confidence: 51%
“…Munc18-2 fully restored docking in chromaffin cells, although the cognate syntaxin partner for Munc18-2 is syntaxin3 (Riento et al, 2000). This observation provides an opportunity for investigating whether there are additional aspects to the function of Munc18 proteins beyond vesicle docking.…”
Section: Differential Priming By Isoforms Reveals An Additional Intermentioning
confidence: 98%
“…Previous studies have suggested that Munc18-2 can interact with the monomeric Syntaxins STX3 (39,40), STX2 (41), and STX11 (13,(33)(34)(35). However, other SM proteins have distinct binding modes in which they engage either monomeric syntaxins or SNARE complexes (42-45).…”
Section: Resultsmentioning
confidence: 99%
“…Proteins of SNARE complex are known to play a role in the regulation of the direct apical biosynthetic route: t-SNARE syntaxin-3 and v-SNARE Ti-VAMP (36,37,44,45). In addition, the sec1-related protein Munc18-2 modulates the interaction of syntaxin-3 with other SNARE partners, and controls the vesicular apical transport (38). Annexin XIIIb has been also previously described to play a role in apical delivery through an association with rafts (40).…”
Section: Discussionmentioning
confidence: 99%
“…The t-SNAREs syntaxin-3 and -4 were, respectively, localized at the apical and basolateral membranes of polarized MDCK and Caco-2 cells (36, 37). Munc18-2/Munc18b is a Sec1 homologue, which interacts with the apical t-SNARE syntaxin-3 (38). Annexin XIIIb is an N-myristoylated protein, which was reported to participate in the apical transport via an association with the raft lipid microdomains (39,40).…”
Section: Alteration In the Distribution Of Endogenous Human Dpp-iv-wementioning
confidence: 99%